Ethnography and Cognitive Task Analysis to Elicit Expert Knowledge in Perceptual-Motor Tasks - Angela L.S. Tan; Rosemary R. Seva; Martin G. Helander (Faculty of Psychology, Universitas Surabaya, 2006)
-